Student Perceptions of the Program Component Effectiveness of a Leisure and Sport Management Program (LSM) - Jim K. Rost; Colby B. Jubenville (Journal of Applied Sports Management, 2015)
Although the trend in higher education is moving toward an emphasis on institutional mission-based funding and retention plans, little has been done to evaluate students' perceptions of academic program effectiveness and an integration of a total quality management approach to ensuring program quality. The purpose of this study was to determine what effect student perception of Leisure and Sport Management (LSM) program components had on their perception of overall program quality with regard to Deming's 14 points of Total Quality Management. Forty-eight students from a graduate LSM program completed one questionnaire, comprised of three demographic variables and 29 attitude items. Four subfactors of program component effectiveness and one factor of overall program quality were analyzed through hierarchal multiple regression. Results indicated that when controlling for gender, age, and program classification, student perception of program component effectiveness is directly related to their perception of overall program quality. Moreover, students had a positive perception of LSM program components, Academic and Career Preparation and Commitment to Academic Excellence, in particular.
Keywords: student retention; program effectiveness; Total Quality Management